Italian-Canadian Narratives of Return Analysing Cultural Translation in Diasporic Writing - Baldo, Michela; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book examines the concept of translation as a return to origins and as restitution of lost narratives, and is based on the idea of diaspora as a term that depicts the longing to return home and the imaginary reconstructions and reconstitutions of home by migrants and translators. The author analyses a corpus made up of novels and a memoir by Italian-Canadian writers Mary Melfi, Nino Ricci and Frank Paci, examining the theme of return both within the writing itself and also in the discourse surrounding the translations of these works into Italian. These 'reconstructions' are analysed through the lens of translation, and more specifically through the notion of written code-switching, understood here as fictional tool which symbolizes the translational movements between different points of view. This book will be of particular interest to students and scholars of translation and interpreting, migration studies, and Italian and diasporic writing. Michela Baldo is Honorary Fellow in Translation Studies in the Department of Modern Languages and Cultures at the University of Hull, UK.
Chapter 1: Introduction: Translation, narratives and returns -- Chapter 2: Italian-Canadian writing and narratives of translation as return: The Italian translations of Ricci's trilogy, Melfi's Italy revisited and Paci's Italian Shoes -- Chapter 3: Towards a Narrative Model of Code-switching in Diasporic Writing -- Chapter 4: Code-switching and return in Ricci, Melfi and Paci and in the Italian translations of their works -- Chapter 5: Return as restoration and restitution -- Chapter 6: Conclusions. .
Keywords: Translating and interpreting; Comparative literature; Emigration and immigration; America -- Literatures; Fiction; Sex; Language Translation; Comparative Literature; Human Migration; North American Literature; Fiction Literature; Gender Studies